2015
DOI: 10.1002/2327-6924.12190
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioner knowledge, use, and referral of complementary/alternative therapies

Abstract: Purpose The study aims are to (a) describe nurse practitioners' (NPs') belief in effectiveness, knowledge, referral, and use of complementary/alternative therapies (C/ATs), (b) explore the initiation of C/AT dialogue between NPs and their patients, and (c) examine the relationships between demographic variables and NP C/AT knowledge, beliefs, use, referrals. Data sources A mixed‐method cross‐sectional online survey of licensed NPs (N = 2874) from a Midwestern state was analyzed using descriptive statistics, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
4
12
0
3
Order By: Relevance
“…Consistent with the literature (Geisler et al, 2014;Jones et al, 2017;Trail-Mahan et al, 2013), the nurse respondents reported positive attitudes toward CAM. Specifically, medical-surgical, ED, and perioperative nurses scored higher on CAMBI total score.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with the literature (Geisler et al, 2014;Jones et al, 2017;Trail-Mahan et al, 2013), the nurse respondents reported positive attitudes toward CAM. Specifically, medical-surgical, ED, and perioperative nurses scored higher on CAMBI total score.…”
Section: Discussionsupporting
confidence: 85%
“…This difference could be linked with environmental factors; as the use of CM is higher among oncology patients, oncology nurses might be more in contact with CM, and thus feel more knowledgeable about it. The lack of communication and the unease of healthcare professionals discussing CM has already been described [ 11 ], with females, CM users and knowledgeable professionals being more likely to recommend CM to patients [ 39 ]. These results correlate with ours, that female and CM trained professionals were more likely to start a discussion about CM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in different countries on the level of knowledge, attitude and practice of CAM in the clinical setting had different results. In a study in Turkey, it was found that 74.8% of health personnel were practising CAM in the clinical setting (Midilli et al., 2016); also, another study on nurse practitioners showed that 85% of them referred their patients for massage or bodywork, which are types of CAM (Geisler et al., 2015), and results of a study on 362 nursing assistants showed that CAM usage prevalence among nurses was 92.4% (Bahall, 2017). The study in Turkey showed that 81.7% of health personnel had a moderate to good level of knowledge in this regard (Midilli et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The study in Turkey showed that 81.7% of health personnel had a moderate to good level of knowledge in this regard (Midilli et al., 2016). Also, in one study, 95% of nurses believed that nurse practitioners should have knowledge about CAM (Geisler et al., 2015). More than half of the health personnel in the study conducted in Turkey had a positive attitude towards CAM (Midilli et al., 2016) and a review study supported it and showed that 66.4% of nurses had a positive attitude toward CAM (Bahall, 2017).…”
Section: Introductionmentioning
confidence: 99%